Enhancing sexual health and empowerment among migrant women sex workers: a community health worker-led intervention in Marseille, France - Mosnier, Emilie; Hoyer, Maxime; Artigas, Fernanda; Regnault, Hippolyte; Richard, Elodie; Michels, David; Mosnier, Marine; Inegbeze, Grâce; Robledo, Manuela Salcedo; Spire, Bruno; Vandentorren, Stéphanie; Lescaudron, Marc; et al. (Frontiers in Public Health, 2024)
Introduction Given the high infection rate of sexually transmitted infections (STI) among migrant women sex workers (WSWs), it is necessary to understand how to improve prevention, information and care for this vulnerable population. Community health workers (CHWs), by linking community to health services, are positioned to improve health outcomes in migrant communities. This article aims to describe a pilot innovative intervention performed by CHWs to improve sexual health in migrant WSWs. Methods This one-year intervention study used a Respondent-driven sampling (RDS) to recruit a representative cohort of migrant WSWs in Marseille, France. Four CHWs were recruited from different communities and participated in all stages of the research. They performed individual and group interventions of prevention, support in care and empowerment. Data on participant characteristics, type of intervention and adherence to the intervention were reported via questionnaires given to participants. Simultaneously, semi-structured interviews and informal interviews of migrant WSW, CHWs and care providers were carried out. Results A total of 132 migrant WSWs were included in the cohort. Very few of them knew about PrEP (12%) or already used HIV post-exposure treatment (9%). Migrant WSWs were often victims of rape or racism, 15 and 21% respectively. In two-thirds of cases the level of health literacy was low. Participants suffered from a combination of vulnerability factors: difficulties with access to social rights, food or housing. Only 13% reported having benefited from medical follow-up or assistance by an NGO in the 3 months prior to the program. By 3 months, more than one third of the participants had been tested for HIV (35%) and 63% knew about PrEP. A total retention rate of 70% was reported in the cohort after 6 months.